The Court-Martial of Paul Revere : A Son of Liberty and America's Forgotten Military Disaster - Greenburg, Michael M. (Book collections on Project MUSE., 2014)
Examines Paul Revere's pursuit of a court-martial in order to resuscitate his reputation following the military disaster of the Penobscot Expedition, in which he served as the artillery commander.